Relationship Between Estradiol and Hemostasis Determined Through Thromboelastography Profile in Controlled Ovarian Stimulation Cycles - Permadi, Wiryawan (J Blood Med, 2021)
PURPOSE: We aimed to analyze the relationship between estradiol level and thromboelastography profile. PATIENTS AND METHODS: This prospective study with comparative analysis was performed on nineteen samples undergoing an IVF procedure in two fertility clinics in Bandung city. Blood samples taken on the second and twelfth days of the IVF cycle. RESULTS: There were significant differences in the value of estradiol, fibrin formation time (α), and coagulation index (CI) (p<0.05). Correlation tests showed no relationship and no significant correlation between an increased level of estradiol and coagulation index (CI) (r(s)=0.054; p=0.827) and between an increased level of estradiol and fibrinolysis time (LY30) (r(s)=−0.151; p=0.536). A moderate significant relationship was observed between age and coagulation index (CI) (r(s)=−0.430; p=0.033) and between age and maximum amplitude (MA) (r(s)=−0.494; p=0.032). CONCLUSION: Supraphysiological estradiol levels in controlled ovarian stimulation cycles affect the coagulation index and change mainly the fibrin formation time.